Mexico attempts to tackle obesity: the process, results, push backs and future challenges. (23rd October 2013) - Barquera, S.; Campos, I.; Rivera, J. A.
Summary: Mexico's obesity prevalence is one of the world's highest. In 2006, academics, and federal and state government agencies initiated efforts to design a national policy for obesity prevention. The Ministry of Health (MOH) established an expert panel to develop recommendations on beverage intake for a healthy life in 2008. Subsequently, the MOH, with support from academia, initiated the development of the National Agreement for Healthy Nutrition (ANSA). ANSA was signed by all relevant sectoral actors in 2010 and led to initiatives banning sodas and regulating unhealthy food in schools and the design of other yet to be implemented initiatives, such as a front‐of‐package labeling system. A main challenge of the ANSA has been the lack of harmonization between industry interests and public health objectives and effective accountability and monitoring mechanisms to assess implementation across government sectors. Bold strategies currently under consideration include taxation of sugar‐sweetened beverages, improvement of norms for healthy food in schools, regulation of food and beverage marketing to children and implementation of a national front‐of‐pack labeling system. Strong civil society organizations have embraced the prevention of obesity as their goal and have used evidence from academia to position obesity prevention in the public debate and in the government agenda.